(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
The results of piles tests in sea muddy soils underlain by loams and clays are presented at port berths in Odessa region. Piles length 28.0 and 34.0 m have been made of metal pipes with a diameter of 1400 mm with a wall thickness of 16 mm. From the sea water surface to the silt roof is 15.0 m. The lower end of the two tubular supports (piles) has been located above the silt sole that enables the test piles to be brought to "breakdown" and determine its resistance (silt) along the outer and inner surfaces. According to the test results, the piles are increased by 6 m that enables to use the underlying soils as a bearing layer. Tests of piles have been carried out according to the standard procedure, for the reference system, two additional tubular supports with a diameter of 1400 mm were placed in the vicinity of the test subjects.